Uso de métodos clássicos e bayesianos em modelos de regressão beta - Reitman, Diomedes Pael (Universidade Federal de São Carlos, 2007)
This work involves a study of a regression model appropriated for situations which the response variable is measured in a continuous scale in the (0, 1) interval, as, for instance, taxes or proportions. The developed inferences were based on the Classic and Bayesian methodology. A discussion about the application of the beta regression model is presented.
Keywords: Análise de regressão; Inferência bayesiana; MCMC; Beta regression model; Beta distribuition; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA